Emergency Care Gap in Brazil: Geographical Accessibility as a Proxy of Response Capacity to Tackle COVID-19 - Silva, Lincoln Luís; Carvalho Dutra, Amanda de; Andrade, Luciano de; Iora, Pedro Henrique; Rodrigues Ramajo, Guilherme Luiz; Peres Gualda, Iago Amado; Costa Scheidt, João Felipe Hermann; Vasconcelos Maia do Amaral, Pedro; Hernandes Rocha, Thiago Augusto; Staton, Catherine Ann; Nickenig Vissoci, João Ricardo; Fressatti Cardoso, Rosilene (Frontiers in Public Health, 2021)
Background: The new coronavirus disease (COVID-19) has claimed thousands of lives worldwide and disrupted the health system in many countries. As the national emergency care capacity is a crucial part of the COVID-19 response, this paper evaluated the Brazilian Health Care System response preparedness against the COVID-19 pandemic. Methods: A retrospective and ecological study were performed with data retrieved from the public national healthcare database. The numbers of intensive care (ICU) and hospital beds, general or intensivist physicians, nurses, nursing technicians, physiotherapists, and ventilators from each regional health entity were extracted. The beds per health professionals and ventilators per population rates were assessed. A health service accessibility index was created using a two-step floating catchment area. A spatial cluster analysis using Getis-Ord Gi* was performed to highlight areas with a lack of access to emergency care services (ECS). Results: As of February 2020, Brazil had 35,682 ICU beds, 426,388 hospital beds, and 65,411 ventilators. In addition, 17,240 new ICU beds were acquired by June 2020. The south and southeast regions have the highest rates of professionals and infrastructure to attend patients with COVID-19 compared to the northern region. The northern region has the lowest accessibility to ECS. Conclusions: Brazilian Health Care System is unevenly distributed. The inequitable distribution of health facilities, equipment, and human resources lead to inadequate preparedness to manage the COVID-19 pandemic, and where high rates of morbidity and mortality are expected from COVID-19.